Natural enemy–herbivore networks along local management and landscape gradients in urban agroecosystems. Issue 8 (28th July 2020) - Philpott, Stacy M.; Lucatero, Azucena; Bichier, Peter; Egerer, Monika H.; Jha, Shalene; Lin, Brenda; Liere, Heidi
Abstract: Ecological networks can provide insight into how biodiversity loss and changes in species interactions impact the delivery of ecosystem services. In agroecosystems that vary in management practices, quantifying changes in ecological network structure across gradients of local and landscape composition can inform both the ecology and function of productive agroecosystems. In this study, we examined natural‐enemy–herbivore co‐occurrence networks associated with Brassica oleracea (cole crops), a common crop in urban agricultural systems. Specifically, we investigated how local management characteristics of urban community gardens and the landscape composition around them affect (1) the abundance of B. oleracea herbivores and their natural enemies, (2) the natural‐enemy : herbivore ratio, and (3) natural‐enemy–herbivore co‐occurrence network metrics. We sampled herbivores and natural enemies in B. oleracea plants in 24 vegetable gardens in the California, USA central coast region. We also collected information on garden characteristics and land‐use cover of the surrounding landscape (2 km radius). We found that increased floral richness and B. oleracea abundance were associated with increased parasitoid abundance, non‐aphid herbivore abundance, and increased network vulnerability; increased vegetation complexity suppressed parasitoid abundance, but still boosted network vulnerability. High agricultural land‐use cover in the landscape surrounding urban gardens was associated with lower predator, parasitoid, and non‐aphid herbivore abundance, lower natural‐enemy : herbivore ratios, lower interaction richness, and higher trophic complementarity. While we did not directly measure pest control, higher interaction richness, higher vulnerability, and lower trophic complementarity are associated with higher pest control services in other agroecosystems. Thus, if gardens function similarly to other agroecosystems, our results indicate that increasing vegetation complexity, including trees, shrubs, and plant richness, especially within gardens located in intensively farmed landscapes, could potentially enhance the biodiversity and abundance of natural enemies, supporting ecological networks associated with higher pest control services.